2008
DOI: 10.1093/jnci/djn065
|View full text |Cite
|
Sign up to set email alerts
|

Results at Recruitment From a Randomized Controlled Trial Comparing Human Papillomavirus Testing Alone With Conventional Cytology as the Primary Cervical Cancer Screening Test

Abstract: For women aged 35-60 years, HPV testing with a cutoff of 2 pg/mL achieves a substantial gain in sensitivity over cytology with only a small reduction in PPV. Among women aged 25-34 years, the large relative sensitivity of HPV testing compared with conventional cytology and the difference between relative sensitivity during phases 1 and 2 suggests that there is frequent regression of CIN2+ that are detected by direct referral of younger HPV-positive women to colposcopy. Thus, triage test or repeat testing is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
241
1
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(268 citation statements)
references
References 27 publications
11
241
1
15
Order By: Relevance
“…In addition, HPV‐positive women with cytology less than ASCUS were directly referred to colposcopy if aged 35–60 years,14 while those aged 25–34 years were referred to colposcopy only if after 1 year HC2 remained positive or cytology was ASCUS or greater 15. During phase 2, women in the HPV arm were referred for colposcopy if the HPV test was positive 16. Therefore, in the experimental arm, management at recruitment varied by phase and age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HPV‐positive women with cytology less than ASCUS were directly referred to colposcopy if aged 35–60 years,14 while those aged 25–34 years were referred to colposcopy only if after 1 year HC2 remained positive or cytology was ASCUS or greater 15. During phase 2, women in the HPV arm were referred for colposcopy if the HPV test was positive 16. Therefore, in the experimental arm, management at recruitment varied by phase and age.…”
Section: Methodsmentioning
confidence: 99%
“…The same exercise was repeated at the time of the second screening round. The results of such reviews were previously reported 14, 16, 17, 22, 23. Adenocarcinoma in situ was considered with CIN3.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] The few follow-up studies have focused on pre-invasive lesions and on the length of reassurance that a negative test provides. [6][7][8][9][10] Only few studies have had emphasis on public health aspects.…”
mentioning
confidence: 99%
“…Large longitudinal studies have shown that screening can be improved by the introduction of a hrHPV test as a primary screening tool [14][15][16][17][18][19][20][21][22][23][24][25][26]. Compared to primary screening with Pap cytology, a primary hrHPV test has a superior sensitivity for cervical cancer [24] and its high-grade precursor lesions (cervical intraepithelial neoplasia grade 3, CIN3) [14][15][16][17][18][19][20][21]26]. Moreover, a negative hrHPV test has been shown to provide a significantly higher long-term reassurance against the presence or development of CIN3 or cervical cancer (together referred to as ≥CIN3) compared to a normal Pap cytology result [22,23].…”
Section: Introductionmentioning
confidence: 99%